2012
DOI: 10.3348/kjr.2012.13.3.300
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Modified Pharmacomechanical Thrombolysis Technique for Endovascular Treatment of Thrombosed Prosthetic Arteriovenous Grafts

Abstract: ObjectiveWe applied a modified pharmacomechanical thrombolysis (PMT) technique to endovascular treatment of thrombosed arteriovenous (AV) grafts without the use of any mechanical thrombectomy devices. The aim of this study was to evaluate the efficacy of the PMT technique in the treatment of thrombosed AV grafts by analyzing the long-term patency.Materials and MethodsEighty-two patients with thrombosed AV grafts were treated with the PMT technique. AV graft surveillance to detect failing/failed access was foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…P atent vascular access is critical for patients with kidney failure who rely on regularly scheduled hemodialysis. Detailed evidence-supported guidelines have been developed regarding vascular access placement (1)(2)(3)(4), and much has been written about the surveillance, maintenance, biology, cost, and interventional techniques for these accesses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Similarly, predictors of success following radiological intervention of these access sites have been evaluated, including pressure, the degree of stenosis, and procedure type (16,17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P atent vascular access is critical for patients with kidney failure who rely on regularly scheduled hemodialysis. Detailed evidence-supported guidelines have been developed regarding vascular access placement (1)(2)(3)(4), and much has been written about the surveillance, maintenance, biology, cost, and interventional techniques for these accesses (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Similarly, predictors of success following radiological intervention of these access sites have been evaluated, including pressure, the degree of stenosis, and procedure type (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…Percutaneous endovascular techniques have proven to be successful with the added benefits of lower cost and periprocedural morbidity when compared to surgical thrombectomy (3,11). Studies have shown that surveillance of indwelling arteriovenous (AV) grafts can reduce the number of thromboses, and that procedure technique can influence success (11,12,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The patency status of the AVF was documented 2 to 40 hours from the thrombus infiltration in an interventional radiology suite by contrast fistulography. One or two 5‐ to 7‐Fr introducer sheath (Terumo, Tokyo, Japan) was inserted into the fistula, and angioplasty of culprit stenosis was performed using a balloon catheters with diameters from 4 to 12 mm (Abbott Vascular, IL, USA or Boston Scientific, MA, USA) . Residual thrombi were managed either by manual thromboaspiration or by mechanical fragmentation techniques.…”
Section: Methodsmentioning
confidence: 99%
“…12 Percutaneous endovascular techniques have proven to be successful, with the added benefits of periprocedural morbidity when compared with surgical thrombectomy. 12,13 Studies have shown that surveillance of indwelling AV grafts can reduce the number of thromboses, and that this procedure technique can influence success. 12,14 Today, modern endovascular thrombectomy devices that use different methods of thrombus fragmentation and transportation are commercially available.…”
Section: Discussionmentioning
confidence: 99%